2017
DOI: 10.1002/mc.22705
|View full text |Cite
|
Sign up to set email alerts
|

PTENP1 inhibits the growth of esophageal squamous cell carcinoma by regulating SOCS6 expression and correlates with disease prognosis

Abstract: PTEN pseudogene (PTENP1) has a tumor suppressive role in multiple cancers. However, its involvement in esophageal squamous cell carcinoma (ESCC) remains largely unknown. In this study, we set out to identify the role of PTENP1 in the development of ESCC. Gene Expression Omnibus database was employed to investigate the expression of PTENP1 in ESCC. sRNA target Database (StarBase v2.0) was used to query the downstream of PTENP1. Next, both in vitro and in vivo experiments were employed to explore the function. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 40 publications
(117 reference statements)
0
18
0
Order By: Relevance
“…The subsequent western blot assay confirmed that miR‐548d‐3p intensified JAK–STAT pathway through suppressing expression of SOCS5 and SOCS6. In addition, our research indicated that miR‐548d‐3p accelerated the behaviors of OSCC cells via JAK–STAT pathway, which was recognized as one of the major oncogenic signaling pathways activated in a variety of human malignancies .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The subsequent western blot assay confirmed that miR‐548d‐3p intensified JAK–STAT pathway through suppressing expression of SOCS5 and SOCS6. In addition, our research indicated that miR‐548d‐3p accelerated the behaviors of OSCC cells via JAK–STAT pathway, which was recognized as one of the major oncogenic signaling pathways activated in a variety of human malignancies .…”
Section: Discussionmentioning
confidence: 82%
“…Given that SOCS5 and SOCS6 are known to be potential tumor suppressors , we reasoned that miR‐548d‐3p might play an important role on biological behaviors of OSCC cells by targeting SOCS5 and SOCS6. We structured the cells with overexpression of SOCS5 or SOCS6 effectively (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor suppressive role of PTENP1 in esophageal squamous cell carcinoma was reported by Gong et al (2017). They found a downregulated expression of PTENP1 in esophageal squamous cell carcinoma compared with the corresponding adjacent normal tissues and overexpression of PTENP1 inhibited tumor proliferation (esophageal squamous cell carcinoma).…”
Section: Esophageal Squamous Cell Carcinomamentioning
confidence: 87%
“…27 In addition, enhanced expression of PTENP1 inhibited cell growth, migration in esophageal squamous cell carcinoma or breast cancer by regulating SOCS6 or miR-19b, respectively. 28,29 Therefore, it is imperative to disclose the role of PTENP1 in cisplatin resistance of BC cells. As bioinformatics analysis by online database MiRcode, PTENP1 could specically bind to miR-103a.…”
Section: Discussionmentioning
confidence: 99%